2013
DOI: 10.5012/bkcs.2013.34.3.851
|View full text |Cite
|
Sign up to set email alerts
|

Re-synthesis and Electrochemical Characteristics of LiFePO4Cathode Materials Recycled from Scrap Electrodes

Abstract: This paper describes an environmentally friendly process for the recovery of LiFePO 4 cathode materials from scrap electrodes by a simple thermal treatment method. The active materials were easily separated from the aluminum substrate foil and polymeric binders were also decomposed at different temperatures (400 o C, 500 o C, 600 o C) for 30 min under nitrogen gas flow. The samples were characterized by X-ray diffraction (XRD), scanning electronic microscopy (SEM), Raman spectroscopy, Thermogravimetric analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…These results were in agreement with those reported by Zucolotto et al who suggested a two steps mechanism starting with the evaporation of HF followed by carbon chain scission [96]. Beyond the decomposition of the binder, thermal treatment allows the destruction of other organic contaminants, recrystallization of the active material, and regeneration of the carbon coating [69,97,98]. According to Kim et al, the carbonization of the binder during the thermal treatment of LFP black mass in N 2 atmosphere increased the electrical conductivity of the active material and enhanced its electrochemical performance [69].…”
Section: Removal Of Current Collector and Bindersupporting
confidence: 92%
See 3 more Smart Citations
“…These results were in agreement with those reported by Zucolotto et al who suggested a two steps mechanism starting with the evaporation of HF followed by carbon chain scission [96]. Beyond the decomposition of the binder, thermal treatment allows the destruction of other organic contaminants, recrystallization of the active material, and regeneration of the carbon coating [69,97,98]. According to Kim et al, the carbonization of the binder during the thermal treatment of LFP black mass in N 2 atmosphere increased the electrical conductivity of the active material and enhanced its electrochemical performance [69].…”
Section: Removal Of Current Collector and Bindersupporting
confidence: 92%
“…Similar thermal reactivation processes were explored for LFP batteries, notably by Kim et al [69]. In the process of Kim et al, after opening of batteries and sorting their components, the cathode was submitted to thermal treatment at 500 • C under nitrogen flow.…”
Section: Direct Recycling Approachmentioning
confidence: 98%
See 2 more Smart Citations
“…15 The use of SBR as watersoluble binder in LiFePO 4 cathode material as a substitute of PVdF binder has already been reported in the literature. [16][17][18] The recipe used in this work is based on descriptions in the literature. 19 In future work, the recipes for the cathode will be further optimized.…”
Section: B Experimentalmentioning
confidence: 99%